Identification of Internal Factor Affecting Tourism Business Performance in Jembrana Regency of Bali - Gandhiadi, G K; Kencana, Eka N (Jurnal Matematika; Vol 9 No 1 (2019)DO - 10.24843/JMAT.2019.v09.i01.p110, 2019)
Abstract : T he tourism industry in Jembarana Regency of Bali is currently still hobbling. His contribution to the Jembrana Regional budget is still very minimal. Indeed accessibility to tourist destinations in Jembrana is often an obstacle for tourists, but internal factors that affect the performance of Jembrana tourism businesses are very important to be studied and analyzed, especially for tourism businesses actors and the role of government of the Jembrana Regency. Internal factors in tourism business are strongly influenced by the capacity of social capital, entrepreneurial culture of tourism actors and the role of the government in the development of tourism business.   Based on a survey and structured interviews on 75 tourism entrepreneurs in Jembrana Regency of Bali, modeling by SEM-PLS with the help of Smart PLS 3.0 software, the results obtained are: (1) structural equation model has met the appropriate qualifications, the measurement model obtained is valid and reliable, while the structural model is quite good, (2) the performance of tourism businesses in Jembrana Regency is positively and significantly influenced by orientation entrepreneurship and the role of government but insignificant influence on social capital, and (3) internal factors that affect the performance of tourism businesses in Jembrana Regency of Bali; sequentially are: entrepreneurial orientation of business people, the role of government in tourism development, and finally the capacity of social capital owned by tourism entrepreneurs.   Key Words : Social Capital, Entrepreneurial Orientation, Role of Government, Tourism Business Performance